HUBUNGAN ANTARA KUALITAS TATA KELOLA PERUSAHAAN DAN KUALITAS LABA DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Zanuba Arifah Chofsoh; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2025)
Earnings quality has become an important issue to discuss after giant companies experienced bankruptcy due to earnings management practices. Companies in Indonesia also experienced the same thing which resulted in a decrease in investor confidence in financial statements. Therefore, the quality of corporate governance needs to be re-examined in relation to earnings quality, both of which are likely to be strengthened by company performance. This study aims to analyze the relationship between corporate governance quality and earnings quality with company performance as a mediating variable. The population in this study consists of companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2020. From the entire population, 154 companies were obtained, resulting in a total sample of 1,078 company-year observations over seven years. This study uses purposive sampling technique. This research data is secondary data obtained from annual reports, financial reports and company websites.The analysis method used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that the quality of corporate governance has no direct effect on earnings quality, the quality of corporate governance has a direct effect on the company's financial performance. Company performance is proven to have a significant effect on earnings quality, which indicates that companies with better performance tend to present higher quality earnings reports. Financial performance mediates the effect of governance quality on the earnings quality of companies listed on the Indonesia Stock Exchange (IDX). This finding confirms the importance of strengthening internal corporate performance in order to improve the transparency and quality of financial information.